2018
DOI: 10.1108/maj-07-2017-1611
|View full text |Cite
|
Sign up to set email alerts
|

An examination of reduced audit quality practices within the beyond the role stress model

Abstract: Purpose The purpose of this paper is to investigate the role stress model originally developed by Fogarty et al. (2000) using more refined measures, a context-specific performance metric and a targeted respondent group. The investigation uses a sample of working professional auditors to investigate the associations between job stressors, burnout and job outcomes using an industry-specific measure of job performance. Design/methodology/approach The analyses use structural equations modeling procedures to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 62 publications
6
35
0
2
Order By: Relevance
“…According to Chong and Monroe (2015), when junior accountants suffer from role ambiguity and role conflict, their level of job burnout increases. In addition, Smith et al (2018) reported that conflict and ambiguity have a positive association with burnout. Recently, Cooper et al (2019) found that role conflict and role overload are related to exhaustion, which is a core dimension of job burnout.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…According to Chong and Monroe (2015), when junior accountants suffer from role ambiguity and role conflict, their level of job burnout increases. In addition, Smith et al (2018) reported that conflict and ambiguity have a positive association with burnout. Recently, Cooper et al (2019) found that role conflict and role overload are related to exhaustion, which is a core dimension of job burnout.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…Several studies have examined the relationship between role stress and burnout in auditors. Several studies have shown a consistent relationship between role ambiguity and burnout (Fogarty et al, 2000;Jones et al, 2010Jones et al, , 2012Mnif & Rebai, 2021;Shbail et al, 2018;Smith et al, 2018), but the study results related to the relationship between role conflict and role overload and burnout are still inconsistent. The study result of (Fogarty et al, 2000;Shbail et al, 2018;Smith et al, 2018) showed that role conflict was positively related to burnout, however (Jones et al, 2010(Jones et al, , 2012Mnif & Rebai, 2021) showed no relationship between role conflict and burnout.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have shown a consistent relationship between role ambiguity and burnout (Fogarty et al, 2000;Jones et al, 2010Jones et al, , 2012Mnif & Rebai, 2021;Shbail et al, 2018;Smith et al, 2018), but the study results related to the relationship between role conflict and role overload and burnout are still inconsistent. The study result of (Fogarty et al, 2000;Shbail et al, 2018;Smith et al, 2018) showed that role conflict was positively related to burnout, however (Jones et al, 2010(Jones et al, , 2012Mnif & Rebai, 2021) showed no relationship between role conflict and burnout. The study result of (Smith et al, 2018) showed that role overload is not associated with burnout, but the results (Fogarty et al, 2000;Jones et al, 2010Jones et al, , 2012Mnif & Rebai, 2021) showed that role overload is positively related to burnout.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…En palabras de Forgarty et al (2000), el síndrome de burnout se encuentra directamente relacionado con la práctica contable, por lo cual se plantea la necesidad de ampliar y profundizar los estudios dependiendo del sector, el área de desempeño y el género, entre otros aspectos, como una herramienta que permita encontrar soluciones (Smith, Emerson, y Boster, 2018). En síntesis, se requiere fortalecer las acciones preventivas que permitan reducir el estrés laboral y de esta manera propiciar el bienestar de los profesionales, lo que debe redundar en salud física y mental, en mejoras en las condiciones de trabajo, la calidad de vida, entre otros aspectos.…”
Section: Conclusionesunclassified